The Effect of Future Orientation and Financial Literacy on Family Retirement Planning Mediated by Saving Attitude - Muhammad Arfan Hajam (Institut Teknologi Sepuluh Nopember, 2020)
One of the ways to plan for a retirement plan is by setting a part of the income or funds owned for future life purposes. Retirement planning for families is carried out so that the finances remain stable when entering retirement. This research aims to determine the effect of future orientation and financial literacy on family retirement planning is mediated by saving attitude. The sample in the research is families in the city of Surabaya. The data used in this research are the primary results of questionnaires with 200 samples and data analysis techniques using SEM-PLS. The results of this research indicate future orientation and financial literacy has a positive effect on family retirement planning and been mediated by saving attitude in city of Surabaya